2009
DOI: 10.1016/j.knee.2008.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Sub-vastus approach is more effective than a medial parapatellar approach in primary total knee arthroplasty: A randomized controlled trial

Abstract: 5In a prospective single-center longitudinal randomized controlled trial 116 patients were 6 allocated to the sub-vastus approach, and 115 to the medial parapatellar approach. At one 7 week follow-up, compared to baseline, range of motion, Knee Society (KS) global, KS 8 knee, and KS pain scores were significantly better in the sub-vastus group. At the one year 9 follow-up WOMAC global and pain scores, SF36 physical function and role-physical 10 scores, and EuroQol utility and pain score were significantly bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
78
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(91 citation statements)
references
References 19 publications
10
78
3
Order By: Relevance
“…This trial found no statistically significant differences in pain scores but did reveal a trend favouring the MPa group at 6 weeks post-operatively, similar to Bridgman et al (2009). The results for pain did not agree with earlier studies that found less pain associated with the SVa (Faure et al, 1993;Cameron, 2001;Weinhardt et al, 2004;Bridgman et al, 2009).…”
Section: -45contrasting
confidence: 76%
See 2 more Smart Citations
“…This trial found no statistically significant differences in pain scores but did reveal a trend favouring the MPa group at 6 weeks post-operatively, similar to Bridgman et al (2009). The results for pain did not agree with earlier studies that found less pain associated with the SVa (Faure et al, 1993;Cameron, 2001;Weinhardt et al, 2004;Bridgman et al, 2009).…”
Section: -45contrasting
confidence: 76%
“…The results for pain did not agree with earlier studies that found less pain associated with the SVa (Faure et al, 1993;Cameron, 2001;Weinhardt et al, 2004;Bridgman et al, 2009). For example, a trial conducted by Cameron, (2001) found less pain in the SVa group at day one post-operatively, but did not state whether the patient or assessor was blinded to the approach, which may have affected the outcome.…”
Section: -45contrasting
confidence: 56%
See 1 more Smart Citation
“…T echniques that reduce injury to the knee extensor mechanism may cause less pain and allow faster recovery of knee function after primary total knee arthroplasty 1 .…”
mentioning
confidence: 99%
“…Quadriceps-sparing (QS) techniques, such as the subvastus approach, avoid incising the quadriceps muscle or tendon by retracting the knee extensor muscles laterally 3 . However, a QS technique can be more difficult in stiff knees or muscular patients, and there is a learning curve for surgeons new to the technique 1,4 . Systematic reviews have indicated that the quality of published trials is poor and no one technique can be considered superior on the basis of the available evidence 2,5 .…”
mentioning
confidence: 99%